The visitor’s satisfaction toward facilities provided in Nature Interpretation Center, Taman Wetland, Putrajaya / Nor Hamalina Abdul Hakim and Ahmad Nazrin Aris Anuar - Abdul Hakim, Nor Hamalina; Anuar, Ahmad Nazrin Aris (Universiti Teknologi MARA, Negeri Sembilan, 2017)
Nature Interpretation Center is hub information that people will be visiting to search more knowledge and getting experience about the nature. The attractive facilities that provided in the center such as exhibition area, entrance foyer and children area will attract visitor to visit. However, it need to be started from design stage so, that can avoid any problem or issues of functions of the facilities. The intention of this paper is to evaluate travel motivation of visitor and to identify visitor’s satisfaction towards facilities that will improve their experience in Nature Interpretation Center. Questionnaire method is used to collect the data and distributed to visitor in Nature Interpretation Center, Putrajaya. This process covers that background of the respondents and facilities that provided in Nature Interpretation Center, Putrajaya.